PENGARUH PEDAGANG KAKI LIMA TERHADAP KENYAMANAN PEJALAN KAKI DALAM PEMANFAATAN TROTOAR (STUDI KASUS JALAN JENDRAL URIP PONTIANAK) - Sitanggang, Yulius; AS, Syafaruddin; Kadarini, Siti Nurlaily (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
As one of the big cities in Indonesia, the level of life activity of Pontianak city community isquite high category. Therefore, one of the priority support required is the availability of adequatefacilities and infrastructure. In Pontianak city, community activities to reach the place (location) ofthe activity center, can be done in two ways namely by means of motor vehicle transportation, andon foot. For the users of vehicles has been provided pathways are arranged in such an orderlymanner. Similarly for pedestrians, there has been a specially provided sidewalk path. But, in facttoday the sidewalks are no longer functioning ideally. Most of the sidewalks in Pontianak City haveswitched functions. The sidewalks are filled with permanent and non-permanent buildings, such asstalls or street vendors, city garden pots, posters and billboards, vehicle parking, mailboxes, policestations and various other buildings. This study aims to find out how the perception of pedestriansabout the convenience of the utilization of the pavement path that has been available in the city ofPontianak, especially in Jalan Jendral Urip Pontianak.The method used in this research is through documentation techniques, questionnaires, andinterview techniques. While for the method of data analysis is by testing the questionnaire throughanalysis of validity test instrument. where the value rxy (value coefficient correlation score grain andtotal score) obtained from the calculation consulted with value r on the product moment table withÎ± = 5%. The questionnaire item is valid if the value is rxy > r tabel. To test the reliability of researchquestionnaire, used alpha analysis technique. The value r11 (instrument reliability value) obtainedfrom the calculation is consulted with the value r in the product moment table with Î± = 5%.Instruments are said to be reliable if the value is r11 > r table.The results of descriptive analysis percentage analysis, (in 5 sampling zones) about theinfluence of street hawkers on the comfort of pedestrians in the utilization of the sidewalk in termsof all factors. With the number of respondents 438 pedestrians, the total score of 11,843, thepercentage of 51.98%, and belonging to the criteria of poor in the utilization of the sidewalk onJalan Jendral Urip Pontianak. From the results of the study that factors include, street hawkers,good sidewalks, appropriate tilt, cleanliness and maintained alertness, good protection, pollutionand odors that should always be observed, as well as ensuring a sense of security, and completenesssupporting facilities, all of which are the main elements that support the sense of comfort in theutilization of the sidewalk on Jalan Jendral Urip Pontianak.Keywords : Street vendors, Pedestrians, Sidewalks.